PROJECT TECHNOLOGIES FOR STUDENTS TRAINING - Сілакова, Т. Т. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article is devoted to project activity organization of higher educational institution students. The project method is presented as a way to implement the tasks of competence-oriented education, aimed not at the integration of actual knowledge, but on their application and acquisition of new ones. The article reflects the main points related to the use of project method in computer science teaching methodology